Hermenêutica existencial em Agostinho de Hipona e Martin Heidegger - Silva, Sérgio Eduardo Lima da (2013)
The thesis presents interpretations of Augustine of Hippo with regard to the first three chapters of genesis, the first book of the Bible. These interpretation are found in the works Literal Commentary on Genesis, concerning Genesis Against the Manicheans, Literal Commentary on Genesis, Unfinished, Books Xi-XIII of the Confessions, as well a brief exposition in Books XI-XIV of the City of God. Exposition of these Augustinian Commentaries seeks to demonstrate various interpretations made by author in one group of texts revealing a hermeneutics centered in the interpreter and not in established interpretive rules. In sequence there is described succinctly the evolution of textual hermeneutics during the modern period up to the reflections conducted by Martin Heidegger in the first half of the twenties. Based in Heidegger s existential commentaries on the Pauline Epistles (Galatians and I-II Thessalonians) and on the tenth Book of the Confessions, there is shown a return to a interpreter-based hermeneutics, such as practiced by Augustine. The concern manifested by Heidegger with regard to given bases foundations, existent in Dasein, foundations which can influence self-comprehension, constitute themselves in possibilities of explication as much for Augustinian interpretive variations, as for the existential approach applied by Heidegger to the Pauline epistles and Augustine s text